Amandemen Konstitusi Dan Implikasinya Terhadap Kelembagaan Negara - Maesaroh (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Within the framework of the legal norm system of the Republic of Indonesia, Pancasila occupies a position as the fundamental norm and the highest legal norm. The hierarchy below it is occupied by the 1945 Constitution. As the basic norm of the state, the discourse on the potential for constitutional amendments, especially related to the 1945 Constitution, is an issue that often arises in public discourse. Constitutional amendment is a process of changing the constitution of a country. This process can have significant implications for state institutions, including the structure and function of state institutions, for example in Indonesia. The results of the analysis show that constitutional amendments can have positive and even negative implications for state institutions. In the reform era, amendments to the 1945 Constitution have resulted in significant changes in the structure of the country's higher institutions.